ANALISIS POTENSI TANAH LONGSOR DI PADANGSARI BANYUMANIK SEMARANG - Setyawan, Agus; Putra, Hisbicus Dwi Surya; Suseno, Jatmiko Endro; Yulianto, Tony (BERKALA FISIKA, 2020)
Semarang city is a city that grew out of old settlement built on alluvial sediment. The conditions cause many natural disasters such as floods and landslides. Padangsari Village, Banyumanik District located in the Southern part with hilly morphology and lithology from Mount.Ungaran. Positive potential is the existences of material for development that are useful for the community, otherwise the negative potential there is soil vulnerability than can cause landslide. Classification of positive and negative potentials is obtained from combining several data and factor such as: rainfall, slope, groundwater level, lithology, sedimentation and landuse. All data were processed with ArcGis softwere and produces a potential map for the Padangsari Village. Hopefully the map will be useful for research and society in Padangsari to produce policy when infrastructure development.Keywords: Landuse, landslide, rainfall, slope, groundwater level, lithology, sedimentation, Padangsari